First-Principles Study of Ni2CrAl Intermetallic Compound with Non-Heusler Phase - Yu, Hai-Li; Duan, Xiao-Hui; Ma, Yong-Jun; Cao, Xu-Han; Zhu, Wen-Jun (Asian Journal of Chemistry, 2012)
The physical properties, such as electronic, elastic and optical properties of Ni2CrAl intermetallic compound with non-Heusler phase have been investigated using first principles based on density functional theory. The calculated elastic constants indicate that Ni2CrAl is mechanically stable. The polycrystalline elastic modulus and Poisson's ratio have been deduced by Voigt-Reuss-Hill approximations. According to the calculated ratio of bulk modulus to shear modulus, Ni2CrAl may be of potential application for ductile materials. The analysis for the band structure reveals that this compound is a conductor. The optical properties have been investigated and the results show Ni2CrAl can strongly reflect the radiation. This is the first theoretical prediction for the properties of Ni2CrAl intermetallic compound with non-Heusler phase and the results need experimental confirmation.